Foxtail Millet [Setaria italica (L.) Beauv.] Grown under Low Nitrogen Shows a Smaller Root System, Enhanced Biomass Accumulation, and Nitrate Transporter Expression - Nadeem, Faisal; Ahmad, Zeeshan; Wang, Ruifeng; Han, Jienan; Shen, Qi; Chang, Feiran; Diao, Xianmin; Zhang, Fusuo; Li, Xuexian (Frontiers in Plant Science, 2018)
Foxtail millet [Setaria italica (L.) Beauv.] is a grain and forage crop well adapted to nutrient-poor soils. To date little is known how foxtail millet adapts to low nitrogen (LN) at the morphological, physiological, and molecular levels. Using the foxtail millet variety Yugu1, we found that LN led to lower chlorophyll contents and N concentrations, and higher root/shoot and C/N ratios and N utilization efficiencies under hydroponic culture. Importantly, enhanced biomass accumulation in the root under LN was in contrast to a smaller root system, as indicated by significant decreases in total root length, crown root number and length, and lateral root number, length, and density. Enhanced carbon allocation towards the root was rather for significant increases in average diameter of the LN-root, potentially favorable for wider xylem vessels or other anatomical alterations facilitating nutrient transport. Lower levels of IAA and CKs were consistent with a smaller root system and higher levels of GA may promote root thickening under LN. Further, up-regulation of SiNRT1.1, SiNRT2.1, and SiNAR2.1 expression and nitrate influx in the root and that of SiNRT1.11 and SiNRT1.12 expression in the shoot probably favored nitrate uptake and remobilization as a whole. Lastly, more soluble proteins accumulated in the N-deficient root likely as a result of increases of N utilization efficiencies. Such ‘excessive’ protein-N was possibly available for shoot delivery. Thus, foxtail millet may preferentially transport carbon towards the root facilitating root thickening/nutrient transport and allocate N towards the shoot maximizing photosynthesis/carbon fixation as a primary adaptive strategy to N limitation.